Halotropism: Phytohormonal Aspects and Potential Applications - Szepesi, Ágnes (Frontiers in Plant Science, 2020)
Halotropism is a salt avoidance tropic response of plants but also can be positive to obtain the optimal salt concentration for some halophytes. Halotropism is important in diverse developmental and stress related processes. Numerous results suggest that this process seems to be under the control and regulation of plant hormone pathway. This minireview collects some recent and fascinating results providing an overview of advances in our understanding of halotropic responses in plants and future applications. The precise hormonal mechanisms by which plant roots perceive salt stress and translate this perception into adaptive, directional growth away from increased salt concentrations are not well understood. This minireview aims to gather recently deciphered information about halotropism focusing potential hormonal aspects. Special attention is focused on comprehensive understanding of halotropism in the view of potential application of this phenomenon.